CURRENT SITUATION AND BARRIERS TO HPV VACCINATION AMONG FEMALE NURSING STUDENTS AT TRA VINH UNIVERSITY, VIETNAM, 2024 - Tai Hoang Hieu, Lam; Le Hoang Giang, Ngo; Lan Trinh, Thach (Journal of Health and Aging, 2025)
Cervical cancer is one of the most common cancers in women and can be prevented through HPV vaccination. However, HPV vaccination coverage in Vietnam remains low, especially among healthcare students. This study aimed to assess the status and barriers to HPV vaccination among female nursing students at Tra Vinh University. A descriptive cross-sectional study was conducted among 233 female nursing students from May to July 2024. Data were collected using a self-administered questionnaire and analyzed with SPSS 22.0, employing descriptive statistics, Chi-square tests, and logistic regression. Only 15.5% of students had received at least one dose of HPV vaccine, with 9.4% completing the full three-dose schedule. The main barriers included high cost (73.4%), concerns about side effects (28.8%), perception of unnecessary vaccination without prior sexual activity (22.3%), and lack of accurate information (21.5%). Most students had good knowledge and positive attitudes: 91.4% knew HPV vaccine prevents cervical cancer, 91.8% trusted its effectiveness, and 92.3% were willing to recommend it to peers. HPV vaccination coverage among female nursing students remains low, largely due to financial constraints and insufficient information. Strengthened health education and financial support policies are essential to improve vaccination uptake in this population.